Adaptive refinement for a local error bound based on duality - Almeida Pereira, Orlando J. B.; Moitinho de Almeida, Jose P. (Computer Assisted Methods in Engineering and Science, 2003)
This paper presents the basis of an adaptive mesh refinement technique aimed at reducing a local error, i.e. the error in a local quantity, which is defined as the integral of a stress or a displacement in a given subregion. Two pairs of dual solutions, one corresponding to the applied load and the other to the virtual action, dual of the local quantity, are used to bound the local error and to provide the element error indicators for the adaptive process. A test case is used to exemplify the behaviour of the technique.